Electronic profiling of algae-derived DNA using DNA-specific Schottky diode - Azmi, Siti Zulfikriyah; Vello, Vejeysri; Rizan, Nastaran; Krishnasamy, Jegenathan; Talebi, Sara; Gunaselvam, Priya; Iqbal, Suhaina Nashath Mohamed; Yew, Chan Yen; Phang, Siew Moi; Iwamoto, Mitsumasa; Periasamy, Vengadesh (Springer, 2018)
In recent years, application of deoxyribonucleic acid (DNA) in electronics has created much interest among researchers because of its unique properties. Important applications involve DNA-based sensors and devices. There are several ways to detect and identify various species of organisms such as polymerase chain reaction, sequencing, as well as microarray techniques. However, these techniques are susceptible to sample contamination, misleading results besides being expensive, and difficult to handle. Herein, we present a novel and low-cost identification method for algae-derived DNA using the electronic properties of DNA. For the first time, current–voltage (I–V) characteristics for selected algae species using DNA-specific diodes were obtained and its corresponding diode parameters (turn-on or threshold voltage, shunt and series resistance, knee voltage, breakdown voltage, as well as breakdown current) were then calculated. We believe this novel technique will benefit mankind in future in terms of medical technology involving pathology and healthcare.